The use of a nonradioactive probe in RFLP analysis of Neurospora crassa DNA - R. J. Radloff; S. R. Engel; C. E. Cords; T. I. Baker (Fungal Genetics Reports, 1989)
Our laboratory is investigating the use of nonradioactive alternatives for the synthesis of DNA probes used in hybridization experiments.